Understanding the role of molecular and genetic alterations in proliferation and progression of oral squamous cell carcinoma : A review article - HIMANSHU SINGH; VEDANT PATEL; DHEERAJ SHARMA; NEERAJ SHARMA; RAHUL A RAZDAN; NENCY PARIHAR (UNIVERSITY JOURNAL OF DENTAL SCIENCES, 2022)
Oral carcinogenesis is known as multifactorial process which engaged plentiful genetic events that transform normal activity of tumor suppressor genes and oncogenes. It is observed that aggregation of genetic alterations is the ground for  advancement of a normal cell to cancer cells, which is known as a multi-step carcinogenesis. Because of this event, growth factor production increases as well as increase in total of receptors on cell surface and increased intracellular signal messengers. The present review scrutinize the existing documentation in the literature related to the oral squamous cell carcinoma. English language articles were searched in various databases such as Pubmed, Scopus, Science direct and Google scholar. The keyword used for searching are “oral squamous cell carcinoma”, “Genetics and Oral squamous cell carcinoma”,“Molecular mechanism in oral squamous cell carcinoma”. The present review spotlights on understanding the molecular mechanism and the genetic factors which is responsible for alteration in the cell which leads to oral squamous cell carcinoma.